Ответ:
Пошаговое объяснение:
4.
( 4 - 14/33 * 1 1/21 ) : 2 2/3 = 1 1/3
1) 14/33 * 1 1/21 = 14/33 * 22/21 = 2/3 * 2/3 = 2 * 2 / 3 * 3 = 4/9
2) 4 - 4/9 = 4/1 - 4/9 = 36/9 - 4/9 = 32/9 = 3 5/9
3) 3 5/9 : 2 2/3 = 32/9 : 8/3 = 32/9 * 3/8 = 4/3 * 1/1 = 4 * 1 / 3 * 1 = 4/3 = 1 1/3
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
Ответ:
Пошаговое объяснение:
4.
( 4 - 14/33 * 1 1/21 ) : 2 2/3 = 1 1/3
1) 14/33 * 1 1/21 = 14/33 * 22/21 = 2/3 * 2/3 = 2 * 2 / 3 * 3 = 4/9
2) 4 - 4/9 = 4/1 - 4/9 = 36/9 - 4/9 = 32/9 = 3 5/9
3) 3 5/9 : 2 2/3 = 32/9 : 8/3 = 32/9 * 3/8 = 4/3 * 1/1 = 4 * 1 / 3 * 1 = 4/3 = 1 1/3